Arrangement of the genome of the human papovavirus RF virus. - Pater, A (1980)
DNA from plaque-purified RF virus, a variant of BK virus, was found to contain two species of molecules. Hybridization of each DNA species to the fragments of BK virus DNA revealed that one species had a deletion corresponding to at least 50% of the late region and the other had a deletion corresponding to at least 40% of the early region of BK virus DNA. Analysis by cleavage of each RF virus DNA species with restriction endonucleases EcoRI, HindIII, AvaII, and PvuII, when compared with BK virus DNA, revealed that the size and number of fragments were different. These results suggest the loss of some restriction sites and the appearance of new sites, probably as a result of base changes in each RF virus DNA species. Furthermore, analysis of the restriction map of each DNA molecule revealed in insertion(s) in both DNA species.